Determinants of Personal Protective Equipment Use Behavior Among Female Farmers of Childbearing Age Exposed to Pesticides in Dempo Selatan District Pagar Alam City - Rizka Tri Ulandari; Imelda Purba; Rafika Oktivaningrum; Muhammad Amin Arigo Saci; Hamzah Hasyim; Yustini Ardillah; Dini Arista Putri (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Female farmers of childbearing age are at risk of adverse health effects due to pesticide exposure in agricultural activities. The use of Personal Protective Equipment (PPE) that does not meet the required standards is one of the factors that causes high pesticide exposure in female farmers of childbearing age. Therefore, the objective of this research was to analyze the factors associated with PPE use behavior among female farmers of childbearing age in South Dempo District of Pagar Alam. This research was a quantitative analytic with a cross-sectional approach. The population of this study was all farmers of childbearing age in the South Dempo District Pagar Alam. A sample of 116 respondents was selected through simple random sampling. Data collection was conducted through interviews using a questionnaire. Data processing was carried out with the stages of editing, coding, entry, and cleaning. Bivariate analysis employed the chi-square test, while multivariate employed the multiple logistic regression. The results of the bivariate analysis showed that there were significant associations between the variables and PPE use behavior: education level, income level, knowledge, attitude, and PPE availability (p-value<0.05). In contrast, age, work period, and agricultural extension worker support were not significantly associated with PPE use behavior (p-value>0,05). The multivariate analysis showed that the most dominant variable determining PPE use behavior was PPE availability. The study concluded that PPE availability was the most determining factor in the PPE use behavior among female farmers of childbearing age.